2019
DOI: 10.1021/acsanm.9b01266
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanofluids as Thermal Management Materials: Molecular Dynamics Study on Orientation and Temperature Effects

Abstract: The dispersion of graphene nanoparticles in a fluid can enhance the thermophysical properties of the base liquid. The physics behind such a phenomenon has yet to be uncovered in the community. In this work, thermal transport in a graphene–water mixture is studied by classical molecular dynamics simulations. Several factors including orientation angle, curvature, thermal rectification, temperature, and van der Waals interaction are investigated, and special attention is paid to the effect on thermal conductance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…In detail, the shear viscosity of composite melt dropped from 4.9 to 0.1 with continuous increase of the temperature in the range of 240°C–260°C, corresponding to the trend change of the color in Figure 4. It was attributed to the degree of molecular thermal motion and molecular entanglement 27,28 . On the other hand, it was clearly observed that the η of composites melt decreased rapidly with the increase of shear rate at 300–2400 S −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In detail, the shear viscosity of composite melt dropped from 4.9 to 0.1 with continuous increase of the temperature in the range of 240°C–260°C, corresponding to the trend change of the color in Figure 4. It was attributed to the degree of molecular thermal motion and molecular entanglement 27,28 . On the other hand, it was clearly observed that the η of composites melt decreased rapidly with the increase of shear rate at 300–2400 S −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Especially, there existed tightly oriented structure at 250°C, which resulted in the powerful entanglement between macromolecules. However, as shown in Figure 3a, with the further increase of temperature, the orientation structure conducive to the entanglement of macromolecules was hard to construct because of the violent movement of macromolecular chains at 260°C 27,28 . On the other hand, the non‐Newtonian of the fluid was weakened at the relatively low temperature, leading to the more steady variation of η and n for the composite melt at 250°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene is the thinnest and strongest material having a two-dimensional (2D) structure with sp 2hybridized carbons [1][2][3]. The material based on graphene has been widely utilized in support of several advanced purposes namely Li-ion batteries, Supercapacitors, etc [4][5][6][7][8][9][10][11][12][13][14][15]. For the synthesis of GO, various synthesis methods in particular thermal reduction [16], chemical reduction [17], electrochemical reduction [18] have been used.…”
Section: Introductionmentioning
confidence: 99%